2012
DOI: 10.3109/01480545.2011.589450
|View full text |Cite
|
Sign up to set email alerts
|

Prior cadmium exposure improves glucoregulation in diabetic rats but exacerbates effects on metabolic dysregulation, oxidative stress, and hepatic and renal toxicity

Abstract: The present study was taken up to assess the role of subchronic exposure to an environmentally relevant dosage of cadmium in type l diabetes. Female rats of the Wistar strain were treated with cadmium (5.12 mg/kg body weight) for 45 days. On day 46, rats were made diabetic by alloxan. After 7 days, diabetes (i.e., animals with serum glucose greater than 300 mg/dL) in the alloxanized animals was confirmed and further experiments were conducted for 15 days. Cadmium pretreatment showed disturbed glucose homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…This is in contrast with some published studies where Cd was reported to increase FBG levels in normal mice or diabetic mice [20,21]. However, our data were consistent with other studies showing that Cd decreased FBG levels [22,23]. The reasons for this discrepancy, and the anomaly of FBG and insulin both decreasing, are unclear.…”
Section: Discussionsupporting
confidence: 73%
“…This is in contrast with some published studies where Cd was reported to increase FBG levels in normal mice or diabetic mice [20,21]. However, our data were consistent with other studies showing that Cd decreased FBG levels [22,23]. The reasons for this discrepancy, and the anomaly of FBG and insulin both decreasing, are unclear.…”
Section: Discussionsupporting
confidence: 73%
“…Experimental studies using adult animals and cell culture models of Cd exposure have shown Cd to have both diabetogenic and antiobesogenic effects (Table 2). Adult female rats (180 days) exposed to high levels of Cd (3.1 ppm) via daily oral gavage for 45 days exhibited hyperglycemia, reduced serum insulin, progesterone and low density lipoproteins (LDL); increased serum estradiol, TGs, very low density lipoproteins (VLDL), and high density lipoproteins (HDL); and reduced glucose clearance at the end of treatment(42). Liver and muscle tissue was harvested and assayed at the termination of the experiment, revealing a significant association between Cd and decreased superoxide dismutase (Sod) and catalase activity, decreased total protein and glycogen content, and increased liver and kidney lipid peroxides (LPO) and serum markers of hepatic dysfunction.…”
Section: Model Systemsmentioning
confidence: 99%
“…In studies, it has been shown that Cd increased hyperglycemia and nephrotoxicity in experimentally induced diabetic animals. It has also been shown in these studies that Cd decreases insulin levels and has direct cytotoxic efficacy on the pancreas (5,7). Type 1 diabetic patients are dependent on exogenous insulin (8).…”
Section: Introductionmentioning
confidence: 82%
“…Cd is regarded greatly toxic and is increasingly bioaccumulated in organism with a biological half-life in people, which is estimated in decades (4). Chronic exposure to Cd results in metal accumulation in tissues and organs, especially in the liver and kidney and causes many histological and metabolic changes, altered gene expression, membrane damage, and apoptosis (5). Cd toxicity is furthermore connected to chancing of redox state and antioxidant system of cells, lipid peroxidation, altered expression of various proteins, and modification in protein structure (6).…”
Section: Introductionmentioning
confidence: 99%